Study of Crystallization Process of Potassium Chloride (KCl) Solution with Ethanol Solution - Selvia Sofi Yanti; Muhimatur Rosida; Ketut Sumada; Caecilia Pujiastuti; Suprihatin Suprihatin (Universitas Islam Raden Rahmat, Malang, 2025)
This study develops a method for producing KCl fertilizer from KCl waste generated during the industrial production of calcium oxide, with KCl concentrations in the wastewater ranging from 7-10%. The main objective of this research was to investigate the effect of ethanol concentration and crystallization time on pore diameter, KCl content, and the amount of product produced. The study was conducted in two stages: evaporation and crystallization. In the evaporation stage, the KCl waste was heated until it reached a saturated solution. In the crystallization stage, ethanol solution was added as an antisolvent to accelerate the crystallization process.KCl analysis results showed that increasing ethanol concentration and crystallization time led to higher K and Cl content in the final product. The highest K content was 79.55%, and the highest Cl content was 16.88%, achieved with 90% ethanol concentration and a crystallization time of 100 minutes. BET analysis indicated that as ethanol concentration increased, the resulting product size grew larger, leading to smaller pore diameters. At high ethanol concentrations, the KCl crystals formed lacked pores. SEM-EDX analysis revealed that the KCl crystals not only contained K and Cl but also other elements such as C, O, and Ca.